2015
DOI: 10.1002/jsfa.7505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hydrophilic head size and hydrophobic tail length of surfactants on the ability of micelles to stabilize citral

Abstract: This work concludes that although the concentration of surfactant could be relevant, if its concentration could be controlled in the same manner as the critical micelle concentration, then a polyethylene alkyl ether-type surfactant with a small hydrophilic head could more efficiently stabilize citral at an acidic pH. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…In addition, there was no relationship between the k values of citral and the interfacial characteristics such as the thickness and density. It has been suggested that iron molecules that accumulate around negatively charged emulsion droplet surfaces at pH 7 are not directly responsible for the degradation of citral in emulsions containing iron (Hong et al, 2016). Although there was no correlation between the thickness and density of the emulsion droplet surfaces and the rate of degradation of citral, here, iron was found to increase the rate of citral degradation in emulsions at pH 3.…”
Section: Influence Of Transition Metals On the Stability Of Citral Incontrasting
confidence: 51%
See 1 more Smart Citation
“…In addition, there was no relationship between the k values of citral and the interfacial characteristics such as the thickness and density. It has been suggested that iron molecules that accumulate around negatively charged emulsion droplet surfaces at pH 7 are not directly responsible for the degradation of citral in emulsions containing iron (Hong et al, 2016). Although there was no correlation between the thickness and density of the emulsion droplet surfaces and the rate of degradation of citral, here, iron was found to increase the rate of citral degradation in emulsions at pH 3.…”
Section: Influence Of Transition Metals On the Stability Of Citral Incontrasting
confidence: 51%
“…Because the micelles formed with the unabsorbed emulsifiers in the aqueous medium have hydrophobic cores that can trap hydrophobic compounds, the micelles could capture lipophilic compounds having relatively high water solubilities and release them into the aqueous phase, and also transport those compounds from one oil droplet to another (Ariyaprakai and Dungan, 2010). Although at acidic pH, the stability of citral incorporated into the hydrophobic interiors of the micelles was improved compared with that of citral in the aqueous phase (Hong et al, 2016), the ability of the micelles to stabilize citral would not be as great as that of the emulsions. However, when micelles are present in emulsions, some citral located in the oil droplets may be transported into the micelles, and the concentration of citral in the aqueous phase of the micelle-containing emulsions would be higher than that in the emulsions containing no micelles.…”
Section: Influence Of Micelles On the Stability Of Citral In Emulsionsmentioning
confidence: 99%
“…Other researchers have also found that the stabilities of neral and geranial are different. For example, Hong et al reported that the release rate of geranial from inclusion complexes was lower than that of neral. The stabilities of geranial and neral were improved effectively by the use of an emulsifier.…”
Section: Resultsmentioning
confidence: 99%
“…Protecting citral from fast degradation and minimizing the primary off‐flavors at low pH have been challenging issues in the food industry for decades. Various methods have been developed to stabilize citral, including spray‐drying, emulsification, micelles and self‐assembly delivery systems . In particular, emulsification has attracted attention because of its simple operation and consistent effects.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous attempts have been made over the years to improve the stability of citral. This included the manipulation of emulsions and micellar solutions, addition of antioxidants, , milk proteins and beet pectin, and catechins in the presence of ferric ions . While many of these attempts have been successful at slowing the rate of degradation, none have been the key to protecting the integrity of citral in acidic conditions over extended periods of time to improve the shelf life of the flavor.…”
Section: Introductionmentioning
confidence: 99%